The Diversity of Contemporary Islamic Economic Thoughts of Schools: Baqir As-Sadr, Mainstream and Alternative - Hendrianto, Hendrianto; Yakin, Ikin Ainul (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Purpose: This study aims to reveal three schools of thought in contemporary times regarding Islamic economic thought in contemporary times, namely the Baqir As-Sadr, Mainstream, and Alternative (critical) schools.Method: This research was conducted with the library (Library Research) data collection using documentation data collection techniques with data analysis, namely content analysis.Findings: The results of this study indicate that contemporary Islamic economics in the first period, the view of the Baqir as-Sadr School, namely Islamic economics is not the same as Islam, Islamic economics must be changed to Iqtishadi, conventional economics needs to be discarded because it is not in accordance with iqtishodi, and the availability of resources is not limited, the two Mainstream schools, that is, not abandoning conventional economics, taking good values from the conventional and then transforming them into sharia, and finally limited resources, the three Alternative schools criticize previous contemporary schools, such as the Baqir As-Sadr school which destroys theories old but still using the old theory. While the Alternative Schools are considered to plagiarize conventional theory, finally Islamic economics needs to be tested for its truth. The three schools provide solutions to contemporary economic progressOriginality: The main contribution in this research lies in disclosing the differences in the three schools of Contemporary Islamic Economics Schools: Baqir As-Sadr, Mainstream, and Alternative